Caracterização do perfil do indivíduo em caso de violência autoprovocada - Roberto, Tiago Moreno Lopes (2019)
The self-provoked violence has occurred in several epidemiological profiles, with various methods of attempts against one's own life, characterizing the attempted suicide, questioning possible interventions for this population that is in greater Psychosocial vulnerability, this work aims to analyze, through notifications, the characterization – in a given world that is in the interior of São Paulo (Votuporanga)-of individuals who went through the health service after trying some Violence against oneself; The period of investigation of occurrences is between January 2015 and June 2017. The collected data were correlated according to location, gender, school level, previous attempts, marital status, sexual option, type of attempt, if you have any mental disorder or mental deficiency among other aspects of relevance; The items that characterize this individual are filled out by the health professionals who welcomed this person who attempted the act against himself, the epidemiological data were essential for s comprehension of the social and multifactorial context found with Greater predominance, predicting possible biopsychosocial actions focused on different sites, adapting to diversified cultures.